If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y + 6 = 8(y + -3) Reorder the terms: 6 + 3y = 8(y + -3) Reorder the terms: 6 + 3y = 8(-3 + y) 6 + 3y = (-3 * 8 + y * 8) 6 + 3y = (-24 + 8y) Solving 6 + 3y = -24 + 8y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-8y' to each side of the equation. 6 + 3y + -8y = -24 + 8y + -8y Combine like terms: 3y + -8y = -5y 6 + -5y = -24 + 8y + -8y Combine like terms: 8y + -8y = 0 6 + -5y = -24 + 0 6 + -5y = -24 Add '-6' to each side of the equation. 6 + -6 + -5y = -24 + -6 Combine like terms: 6 + -6 = 0 0 + -5y = -24 + -6 -5y = -24 + -6 Combine like terms: -24 + -6 = -30 -5y = -30 Divide each side by '-5'. y = 6 Simplifying y = 6
| 4x+x+12-4+2x= | | 315=5x(9) | | 8z+7z=45 | | 6x-(x+2)=3x+11-x | | y-x=100 | | -7(w-2)=4w-8 | | 8z=6z-1 | | 4p-4=2p+44 | | x=0.20x+10 | | 63=-16t^2+64t+3 | | 3-5n-3n=35-72 | | x=0.20x | | -4(m-8)=2m-4 | | 4(6+q)=64 | | 6x-x+2=3x+11-x | | (4x+9x)*(8y+2x)=92 | | -10(-y-9)= | | 7-3x+1=4x+1 | | 142=40(5)+6 | | 142=40(x)+6 | | -(-m+7)= | | -35=5/7u | | 6(-1-6z)=-6 | | 16/5=-8v | | 8x^3+27x^2+54x+27=0 | | 25=-5/3v | | 54+2x=10x-5 | | 5(-3r+9)= | | 10x+12y-2by= | | 4(y-4)+8y=8 | | f(-2)=-3x^2-2x+3 | | 4v/5=8 |